PELANGGARAN HAK ASASI MANUSIA DALAM KEMAJUAN TEKNOLOGI INFORMASI ATAS PINJAMAN ONLINE - ST. Nirwansyah ST. Nirwansyah (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2021)
Setting the protection of personal data is important at this time because various problems arise often with the increasing use of personal data in information technology-based transactions in various aspects of life. The difficulty in taking action against illegal online loan businesses is because there are no regulations that provide strict sanctions against the existence of illegal online loans. These conditions make online loan service users get into problems at the time of collection. In this case, the billing method is sometimes unreasonable by using threats and terror techniques that lead to human rights violations. The protection of the rights of online loan service users is still not optimal even though there are sanctions in the laws and regulations regarding violations of one's right to security through electronic media. This is very concerning considering that online loan service users have basic rights that need to be protected, both as consumers and as humans who have had basic rights since birth.Keywords: Human Rights, Advances in Technology, Information, Online Loans.